(untitled) (Research, Society and Development, 2019)
This study aims to assess the knowledge of the food pyramid for school year the students of final grades of primary school, as well as a proposal for how learning designs can influence the acquisition of these concepts by students. This is a case study in the city of Santa Maria / RS, with students from 6th to 9th grade of a public state school, totaling 158 students. The students answered two questions about the food pyramid be imagined. In both responses, found a better result on the 6th and 8th grade, but students’ understanding of the 6th year achieved a marked improvement in post-test, and this could indicate that the projects developed by teachers in these two groups have obtained best meaningful learning by students.